Anthropometric and leg power factors affect offensive kinetic patterns in fencing - Ntai, A.; Tsolakis, C.; Smirniotou, A.; Paradisis, G. (International Journal of Exercise Science, 2021)
This study aimed to identify potential factors that may influence specific fencing offensive kinetic patterns in a large group of well-trained fencers having different ages, gender level, and training specialization. One-hundred-thirty fencers (males:n= 72) and (females:n= 58), participating in three different fencing weapons (epee, foil, and sabre), having considerable experience of national and international competitions. All members of seven national fencing teams were measured for basic anthropometric parameters, leg power performance and velocity values for three specific kinetic offensive patterns during an International Fencing camp. A multivariate analysis of variance (MANOVA) revealed a significant velocity multivariate effect in age competitive categories (Wilks Delta= 0.129, F= 2.112, p<0.01, n2= 0.060) gender (Wilks Delta= 0.103, F= 3.743, p<0.05, n2= 0.103), competition levels (Wilks Delta= 0.863, F= 5.198, p<0.01, n2= 0.137) and discipline practiced (Wilks Delta= 0.239, F= 4.305, p<0.001, n2= 0.119) respectively. Significant correlations were observed between lunge and step lunge velocity and longjump (LJ), countermovement jump (CMJ), drop jump (DJ), and reaction strength index (RSI). Age, gender, level of participants, and the choice of the weapon practiced, influenced fencing performance. Different leg power abilities could be decisive factors in training schedules design and monitoring training adaptations.